HEAT LOSSES OF BUILDINGS IN VECVARKAVA - Rudzāte, Ineta; Martinovs, Andris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2020)
Uninsulated or poorly insulated buildings cause discomfort to the occupants of these buildings and can increase the cost of thermal energy. It is therefore important to know the heat loss of buildings and which parts of the building are the largest, so that the correct choice of building materials can be ensured so that the building can be completely or partially renovated. This could be insulation of the roof, walls or floor of the building, replacement of windows and doors, which would significantly reduce heat loss.